(untitled) (Biological Sciences - PJSIR, 2022)
The properly dried and defatted mycelium of Rhizopus arrhizus constitutes a naturally immobilized lipase. The mycelium was used to synthesize flavouring esters from fusel oil by esterification in organic solvents. Different parameters like reaction medium, temperature, substrate concentration .and moisture level were optimized for the synthesis of butyrate esters offusel oil. The mycelium was repeatedly used in batch reactions and was found to have high efficiency and good operational stability. The halflife of the mycelial lipase was greatly int1uenced by the concentration of substrates, i.e. the residual activity remained about the same after 20 cycles with low concentrations of substrates (0.1 Meach). However, when concentrations of butyric acid and fusel oil were high, the rhyceliumrapidly lost its activity.